THE INVESTIGATION OF SELF-DEVELOPMENT IS A TYPE OF PERSONAL ACTIVITY - Dadajanova, Dilbar Abdurashidovna (Educational Research in Universal Sciences, 2023)
This article describes the notion of self-development as a type of personality activity of a subject-subject nature its types and stages .